Proximity and journalistic practice in environmental discourse: Experiencing 'job blackmail' in the news. (February 2015) - Johnstone, Barbara; Mando, Justin
The shift from coal to natural gas to fuel electricity generation has positive (environmental) and negative (economic) consequences for people in the affected areas of the US. Representations of the situation in the media shape how citizens understand and respond to it. We explore the role of proximity in media discourse about the closing of a coal-fired power plant near Waynesburg, a small city in a Pennsylvania coal-mining region. Comparing reporting in smaller-circulation newspapers closer to the site with reporting in larger-circulation regional newspapers, we find that Waynesburg-area papers simply describe the events leading to the closure while regional papers analyze the events in larger contexts, and that politicians, not the plant owners, are represented as blaming environmentalists for job loss. Our findings point to the importance of proximity in environmental discourse and to the need to examine not only what kinds of discourse circulate, but also how and to whom.